2018
DOI: 10.1002/biot.201800066
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of Publicly Available Chinese Hamster Ovary (CHO) Cell Transcriptomic Datasets for Identifying Engineering Targets to Enhance Recombinant Protein Yields

Abstract: Transcriptomics has been extensively applied to the investigation of the CHO cell platform for the production of recombinant biotherapeutic proteins to identify transcripts whose expression is regulated and correlated to (non)desirable CHO cell attributes. However, there have been few attempts to analyze the findings across these studies to identify conserved changes and generic targets for CHO cell platform engineering. Here, the authors have undertaken a meta-analysis of CHO cell transcriptomic data and repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…A number of studies have assessed changes in gene expression profiles throughout culture of IgG‐producing CHO cell lines . Of particular relevance to the work reported here are those that report changes in the gene expression related to UPR and ERAD pathways.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have assessed changes in gene expression profiles throughout culture of IgG‐producing CHO cell lines . Of particular relevance to the work reported here are those that report changes in the gene expression related to UPR and ERAD pathways.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Vishwanathan et al (2014) showed that it is not only the increasing copy number of the gene of interest (GOI) during gene amplification that is responsible for higher productivities but also a stepwise change and adaptation of the cell's transcriptome pattern that occurs during the exposure to the selection agents and allows cells to handle higher production challenges. These studies and many others indicate that whether a cell is a high performer or not depends to a large degree on the precise regulation of many genes that contribute to productivity and the fine‐tuned combination of their expression levels (Harreither et al, 2015; Tamošaitis & Smales, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Despite advancements in the ability of CHO cells to reach higher cell concentrations and generate increasing amounts of target biotherapeutic proteins, particularly monoclonal antibodies (mAbs), there remains a desire to further understand the limitations upon CHO cell phenotypes and to engineer cells for the production of more difficult-to-express products (Godfrey et al, 2017;Jossé et al, 2018;Mead et al, 2009). One approach that has been applied toward improving our understanding of the limitations on CHO cell growth and recombinant protein production is the field of transcriptomics (Tamo saitis and Smales, 2018). Transcriptomic studies in particular could benefit from generating material from controlled miniature bioreactors that predict behavior at larger scale, as an issue of such previous studies is reproducibility and robustness across different transcriptomic datasets, given the high heterogeneity of CHO cell lines and their intrinsic genetic instability (Chen et al, 2017;Wurm, 2013;Wurm and Wurm, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of CHO cell and Chinese hamster genome sequences (Lewis et al, 2013;Xu et al, 2011) has greatly enabled omics-based studies (Faustrup Kildegaard et al, 2013), and since there has been an increasing number of publicly available databases for different CHO cell lines. However, the focus of these studies has been on either coding genes or microRNAs (miRNAs), with few studies investigating other classes of RNAs and their impact on CHO cell behavior (Singh et al, 2018;Tamo saitis and Smales, 2018).…”
Section: Introductionmentioning
confidence: 99%